Improving potato (Solanum tuberosum) yield and soil health through integrated nutrient management approach in east coast climatic conditions of India - MOHANTY, M; NANDA, S S; BARIK, A K (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted consecutively for two cropping seasons of 2007-08 and 2008-09 to study the effect of organic (FYM: farmyard manure, vermicompost and neem cake) and inorganic (chemical fertilizers) sources of plant nutrients at different combinations on the growth and yield of potato (Solanum tuberosum L.) tubers and economics besides assessing its impact on soil health in terms of available OC, N,P and K status after its harvest during both the seasons. The experimental soil was slightly acidic (pH 6.4) in nature, low in organic carbon (0.481%), available N (228 kg/ha) and medium in available K (122 kg/ha) and P (18 kg/ha). Results indicated that the application of 50 % recommended dose of fertilizers (RDF) as inorganic sources in conjunction with rest 50% RDF as organic sources as FYM or vermicompost or neem cake (T6, T7 and T8) 15 days before final land preparation, registered significantly higher tuber growth, tuber bulking rate, weight of tubers/plant and yield of potato tubers as compared to rest of the treatments including 100% RDF as inorganic sources alone. Accordingly, the above treatments, on an average, recorded higher tubers yield (19.65 t/ha) to the tune of 6.72, 11.70 and 57.71 % than that of 75% RDF as inorganic fertilizers + 25% as organic manures (FYM or vermicompost or neem cake), 100% RDF as chemical fertilizers and control (no manure or chemical fertilizer), respectively. Moreover, T6, T7 and T8 treatments also exhibited higher uptake of N, P and K from soils in addition to more net returns (Rs. 56993/ha) and benefit: cost ratio (1.94) as compared to rest of the treatments. Integrated nutrient management approach not only proved beneficial in enhancing the yield of potato, but also improved the contents of available organic carbon, N, P and K in treatments where 50% recommended dose of NPK was applied through inorganic and remaining 50% RDF through organic sources.